2019
DOI: 10.3390/ijms20235856
|View full text |Cite
|
Sign up to set email alerts
|

IL-33/IL-31 Axis in Immune-Mediated and Allergic Diseases

Abstract: Several allergic and immunologic diseases including asthma, food allergy (FA), chronic spontaneous urticaria (CSU), atopic dermatitis (AD), systemic lupus erythematosus (SLE), systemic sclerosis (SSc), rheumatoid arthritis (RA), and Behçet’s disease (BD) are characterized by the involvement of Th2 immunity. Several mediators lead to immunoglobulin (Ig)E production, thus including key cytokines such as interleukin (IL)-4, IL-5, and IL-13. Among them, IL-31 and IL-33 have been recently studied as novel biomarker… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
112
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 120 publications
(117 citation statements)
references
References 96 publications
1
112
0
4
Order By: Relevance
“…IL-31 exerts central roles in the pathogenesis and progression of atopic dermatitis and chronic spontaneous urticaria. IL-31, released by CD45RO+ Th2 lymphocytes but also by macrophages, dendritic and eosinophilic cells, mediates the itching in patients suffering from allergic diseases, whereas IL-33, secreted by inflamed or damaged tissue, functions as a local early warning signal [43]. However, although IL-31 primarily induces Th2 responses and allergic manifestations [44], it also suppresses Th2 inflammation [45].…”
Section: The Role Of Il-31 In the Immunoskeletal Interfacementioning
confidence: 99%
See 2 more Smart Citations
“…IL-31 exerts central roles in the pathogenesis and progression of atopic dermatitis and chronic spontaneous urticaria. IL-31, released by CD45RO+ Th2 lymphocytes but also by macrophages, dendritic and eosinophilic cells, mediates the itching in patients suffering from allergic diseases, whereas IL-33, secreted by inflamed or damaged tissue, functions as a local early warning signal [43]. However, although IL-31 primarily induces Th2 responses and allergic manifestations [44], it also suppresses Th2 inflammation [45].…”
Section: The Role Of Il-31 In the Immunoskeletal Interfacementioning
confidence: 99%
“…IL-33 activates naive T cells and promotes their maturation towards a Th2 phenotype, leading to the release of Th2 type cytokines and chemokines. IL-33 influences various adaptive and innate immune cells, including eosinophils, mast cells, type 2 innate lymphoid cells (ILC2), and Th2 lymphocytes [42][43][44]. Via the NF-kB and MAPK signaling pathways, IL-33 induces the production of IL-5, IL-13 and CCL5, CCL17, CCL24 chemokines [57,65].…”
Section: The Role Of Il-33 In the Immunoskeletal Interfacementioning
confidence: 99%
See 1 more Smart Citation
“…Recently was suggested that the IL-31/IL-33 axis could be involved in different conditions such as cancer, autoimmune diseases and allergies [31]. So, this is another interesting and new area to investigate among the complex overlapping mechanisms that connect allergies and osteoporosis (Table 1).…”
Section: Il-33/il-31 Axismentioning
confidence: 99%
“…So, this is another interesting and new area to investigate among the complex overlapping mechanisms that connect allergies and osteoporosis (Table 1). Interleukin-31 (IL-31) is a proinflammatory cytokine, recently indicated as a biomarker of allergic and immunologic diseases, that regulates cell proliferation and play a role in tissue remodelling [31]. It is produced by CD4+ T lymphocytes (Th2 cells) and in lower amounts also by dendritic cells and mast cells.…”
Section: Il-33/il-31 Axismentioning
confidence: 99%